2022
DOI: 10.1080/21655979.2022.2066926
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin impacts deoxyribonucleic acid repair by modulating the mitogen-activated protein kinase pathway in colorectal cancer

Abstract: This study aimed to investigate the effects of luteolin on colorectal cancer (CRC) and explore its underlying mechanism. HCT-116 and HT-29 cells were treated with luteolin, cisplatin, or selumetinib. The cell survival, cell proliferation, apoptosis and cell cycle distribution, and DNA damage were detected using Cell Counting Kit-8, colony formation, flow cytometry, and immunofluorescence staining analysis, respectively. Western blotting was used to detect the expression of apoptosis-related, cycle-related, DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…According to the network diagram, the main active compounds of PS that act on HCC are luteolin, quercetin, β‐sitosterol, pratensein, and chrysoeriol. Luteolin is a flavonoid that can be used as an antitumor agent to prevent tumor cell proliferation, avoid carcinogenic stimuli, activate cell cycle arrest, and induce cell apoptosis through different signal transduction pathways during in vivo and in vitro cancer development (Imran et al., 2019); therefore, luteolin can be a potential antitumor drug (Song et al., 2022). In hepatocytes, the combination of luteolin and 5‐fluorouracil can increase the ratio of BCL2‐associated X (bax)/B‐cell lymphoma‐2 (bcl‐2) and the expression of tumor protein p53 (TP53), enhance the cleavage of polyADP ribose polymerase (PARP), and reduce the content of dihydropyrimidine dehydrogenase (Verschooten et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…According to the network diagram, the main active compounds of PS that act on HCC are luteolin, quercetin, β‐sitosterol, pratensein, and chrysoeriol. Luteolin is a flavonoid that can be used as an antitumor agent to prevent tumor cell proliferation, avoid carcinogenic stimuli, activate cell cycle arrest, and induce cell apoptosis through different signal transduction pathways during in vivo and in vitro cancer development (Imran et al., 2019); therefore, luteolin can be a potential antitumor drug (Song et al., 2022). In hepatocytes, the combination of luteolin and 5‐fluorouracil can increase the ratio of BCL2‐associated X (bax)/B‐cell lymphoma‐2 (bcl‐2) and the expression of tumor protein p53 (TP53), enhance the cleavage of polyADP ribose polymerase (PARP), and reduce the content of dihydropyrimidine dehydrogenase (Verschooten et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Further molecular mechanism studies showed that the Luteolin demonstrated an inhibitory effect on LoVo cells’ proliferation through inhibition of the cell cycle arrest at the G2/M phase transition, inactivating cyclin B1/cell division cycle 2 (CDC2), followed by the induction of apoptosis by cytochrome c- and deoxyadenosine triphosphate-mediated activation of apoptotic protease activating factor 1 [ 50 ]. In a study by Song et al, 2022, Luteolin was found to suppress cell proliferation, cause cell cycle arrest, and induce DNA damage and apoptosis in CRC cells through modulation of the MAPK pathway, while Luteolin inhibited the tumor growth in the CRC xenograft model in vivo [ 51 ]. Additionally, in the same study, Song et al 2022 demonstrated that Luteolin enhanced the effect of one of the most effective chemotherapy drugs, cisplatin, on CRC cells, as the combination of Luteolin and cisplatin caused a significant decrease in cell survival and increased the rate of apoptosis of HCT-116 and HT-29 cells, compared with the only cisplatin treatment [ 51 ].…”
Section: Anticancer Properties Of Luteolin On Different Cancersmentioning
confidence: 99%
“…In a study by Song et al, 2022, Luteolin was found to suppress cell proliferation, cause cell cycle arrest, and induce DNA damage and apoptosis in CRC cells through modulation of the MAPK pathway, while Luteolin inhibited the tumor growth in the CRC xenograft model in vivo [ 51 ]. Additionally, in the same study, Song et al 2022 demonstrated that Luteolin enhanced the effect of one of the most effective chemotherapy drugs, cisplatin, on CRC cells, as the combination of Luteolin and cisplatin caused a significant decrease in cell survival and increased the rate of apoptosis of HCT-116 and HT-29 cells, compared with the only cisplatin treatment [ 51 ].…”
Section: Anticancer Properties Of Luteolin On Different Cancersmentioning
confidence: 99%
“…Poor solubility of flavonoids has always been a daunting task for scientists, being widely researched to explore their hidden therapeutic mechanisms. As discussed above, luteolin is known to inhibit tumorigenesis in a diverse range of cancers by inhibiting the viability, migration, angiogenesis and invasion [ 11 , 12 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. However, the combination of protein and flavonoids can ameliorate the problems of poor solubility and stability of flavonoids for better utilization.…”
Section: Insight Into the Nanodelivery Of Luteolin In Cancermentioning
confidence: 99%